2021
DOI: 10.1111/exd.14361
|View full text |Cite
|
Sign up to set email alerts
|

Senescent cell removal via JAG1‐NOTCH1 signalling in the epidermis

Abstract: Cellular senescence is a phenomenon characterized by irreversible cell cycle arrest. The shortening of telomeres results in cellular senescence and the replicative limit of a cell, as reported by Hayflick. 1 In addition, other reasons such as failure in regulating tumor genes or tumor suppressor genes, DNA damage caused by ionizing radiation or ultraviolet ray (UV) and oxidative stress by reactive oxygen species (ROS) production are also known to cause cellular senescence. 2 Senescent cells increase the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Based on the intensity of the stress and damage, cells may enter senescence prematurely (stress‐induced premature senescence) 80 . Senescent cells exhibit cell cycle arrest mediated by increased levels of p16, p53, and p21, an altered metabolism, macromolecular damage and a senescent‐associated secretory phenotype (SASP) 81–83 . SASP components include inflammatory mediators, growth factors and proteases 84 .…”
Section: Proposed Mechanisms Of the Ha Regulation Of Photoagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the intensity of the stress and damage, cells may enter senescence prematurely (stress‐induced premature senescence) 80 . Senescent cells exhibit cell cycle arrest mediated by increased levels of p16, p53, and p21, an altered metabolism, macromolecular damage and a senescent‐associated secretory phenotype (SASP) 81–83 . SASP components include inflammatory mediators, growth factors and proteases 84 .…”
Section: Proposed Mechanisms Of the Ha Regulation Of Photoagingmentioning
confidence: 99%
“…80 Senescent cells exhibit cell cycle arrest mediated by increased levels of p16, p53, and p21, an altered metabolism, macromolecular damage and a senescent-associated secretory phenotype (SASP). [81][82][83] SASP components include inflammatory mediators, growth factors and proteases. 84 However, the expression of SASP varies markedly from cell to cell.…”
Section: Changes In Mw Of Ha and Hyaluronidases After Uv Radiationmentioning
confidence: 99%
“…We reported that skin inherently possesses mechanisms to remove senescent cells. In the epidermis, this is achieved by the binding of JAG1, a Notch ligand expressed on adjacent non‐senescent keratinocytes, to Notch1 receptors expressed by senescent keratinocytes, which promotes the exclusion of senescent cells from the basal layer by inducing differentiation 3 . Meanwhile, in the dermis, senescent cells are phagocytosed by macrophages through recognition by the phosphatidyl serine (PS) receptor STAB1 4 .…”
Section: Figurementioning
confidence: 99%
“…In the epidermis, this is achieved by the binding of JAG1, a Notch ligand expressed on adjacent non-senescent keratinocytes, to Notch1 receptors expressed by senescent keratinocytes, which promotes the exclusion of senescent cells from the basal layer by inducing differentiation. 3 Meanwhile, in the dermis, senescent cells are phagocytosed by macrophages through recognition by the phosphatidyl serine (PS) receptor STAB1. 4 However, since ageing is associated with the accumulation of senescent cells in skin tissue, it is hypothesized that this accumulation is preceded by a decline in the ability to remove them.…”
mentioning
confidence: 99%
“…Using drug signatures computed from the Gene Expression Omnibus (GEO) database, the common senescence genes were significantly enriched for genes downregulated with metformin (a diabetic drug that alters cell metabolism) and genes upregulated with cisplatin (chemotherapy drug). Notably, the SenoRanger gene set was enriched for genes downregulated with overexpression of JAG1, a NOTCH1 ligand whose decrease in expression with age may reduce Notch signaling and senescent cell clearance in human skin (Yoshioka et al, 2021 ). The SenoRanger genes were also associated with a variety of transcription factors, including CBX2 (ENCODE) which was found to be an essential regulator of senescence‐associated chromosomal instability in mouse fibroblasts (Baumann et al, 2020 ).…”
mentioning
confidence: 99%